Painting with synesthesia translating auditory memory with abstract expressionism - Prado, Gabrielle Marie C.; Feleo, Roberto; Sta Ana, Mary Catherine (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
This thesis was centered on the artist's personal experiences with sound and synesthesia. This discovery informed this work and was documented through the different stages of the artist's life, not as one burdened by these conditions, but as one inspired and informed by it.

The work exhibited were paintings (visual) supported by recorded sounds (audio). These sounds comprised five of the most important stages of the artist's life and environment; hearing for the first time, undergoing speech therapies, learning ballet, taking piano lessons, and discovering synesthesia. From those five moments, the artist chose to exhibit six examples. The recollection did not just focus on the painting, but the act of going back to significant persons in her life: her mother, her audiologist, her ballet teacher, and others; re-enacting and recording the sounds and interpreting them. Because the subject is from the artist's past, the work emphasized the spontaneity of remembering and interpreting through a non-representational and abstract expressionist painting style. The work, albeit spontaneous, was loosely guided by the artist's own visual language which corresponded with specific sounds from synesthetic experiences.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaf 26
Keywords: Synesthesia; Abstract expressionism; Sound; Memory